Association of systolic and diastolic blood pressure and all cause mortality in people with newly diagnosed type 2 diabetes: retrospective cohort study. (30th August 2012) - Vamos, Eszter Panna; Harris, Matthew; Millett, Christopher; Pape, Utz J; Khunti, Kamlesh; Curcin, Vasa; Molokhia, Mariam; Majeed, Azeem
Abstract : Objective To examine the effect of systolic and diastolic blood pressure achieved in the first year of treatment on all cause mortality in patients newly diagnosed with type 2 diabetes, with and without established cardiovascular disease. Design Retrospective cohort study. Setting United Kingdom General Practice Research Database, between 1990 and 2005. Participants 126 092 adult patients (age ≥18 years) with a new diagnosis of type 2 diabetes who had been registered with participating practices for at least 12 months. Main outcome measure All cause mortality. Results Before diagnosis, 12 379 (9.8%) patients had established cardiovascular disease (myocardial infarction or stroke). During a median follow-up of 3.5 years, we recorded 25 495 (20.2%) deaths. In people with cardiovascular disease, tight control of systolic (<130 mm Hg) and diastolic (<80 mm Hg) blood pressure was not associated with improved survival, after adjustment for baseline characteristics (age at diagnosis, sex, practice level clustering, deprivation score, body mass index, smoking, HbA1c and cholesterol levels, and blood pressure). Low blood pressure was also associated with an increased risk of all cause mortality. Compared with patients who received usual control of systolic blood pressure (130-139 mm Hg), the hazard ratio of all cause mortality was 2.79 (95% confidence interval 1.74 to 4.48, P<0.001) for systolic blood pressure at 110 mm Hg. Compared with patients who received usual control of diastolic blood pressure (80-84 mm Hg), the hazard ratios were 1.32 (1.02 to 1.78, P=0.04) and 1.89 (1.40 to 2.56, P<0.001) for diastolic blood pressures at 70-74 mm Hg and lower than 70 mm Hg, respectively. Similar associations were found in people without cardiovascular disease. Subgroup analyses of people diagnosed with hypertension and who received treatment for hypertension confirmed initial findings. Conclusion Blood pressure below 130/80 mm Hg was not associated with reduced risk of all cause mortality in patients with newly diagnosed diabetes, with or without known cardiovascular disease. Low blood pressure, particularly below 110/75 mm Hg, was associated with an increased risk for poor outcomes.